The potency of mexican sunflower extract as the replacement of manure and rice husk charcoal in banana seedling - Andre Sparta; Arifah Rahmi; Panca Jarot Santoso; Ida Fitrianingsih (Jurnal Agro, 2021)
In the nursery, media composition plays an essential role in the growth and development of plant seedlings. Extract of Mexican sunflower (Tithonia diversifolia) could be suitable for replacing organic manure and rice husk charcoal during the seedling phase. The purpose of this study is to examine the ability of Mexican sunflower extract to replace organic manure and rice husk charcoal as the source of nutrients for banana seedling. The study was arranged in a Completely Randomized Design with seven treatments and three replications. Extract of Mexican sunflower promotes plant growth (plant height, number of leaves, and leaf area), improves plant biomass, and improves soil chemical properties (pH (H2O), C organic, and total N). Application twice a week of Mexican sunflower into soil medium resulted superior in plant height, the number of leaves, leaf area, and total biomass of banana seedlings compared to other treatments. Extract of Mexican sunflower could replace organic manure and rice husk charcoal as the nutrient source in banana seedlings. AbstrakPada saat pembibitan, komposisi media memiliki peranan penting terhadap pertumbuhan dan perkembangan bibit tanaman. Ekstrak bunga matahari Meksiko (Tithonia diversifolia) dapat menjadi pilihan yang cocok untuk menggantikan peran dari pupuk kandang dan sekam bakar pada fase pembibitan. Tujuan dari penelitian ini adalah untuk mempelajari kemampuan dari ekstrak bunga matahari Meksiko untuk menggantikan peran pupuk kandang dan sekam bakar sebagai sumber nutrisi bagi bibit pisang. Penelitian ini dilaksanakan dengan menggunakan Rancangan Acak Lengkap dengan tujuh perlakuan dan tiga ulangan. Ekstrak bunga matahari Meksiko dapat meningkatkan pertumbuhan tanaman (tinggi tanaman, jumlah daun, dan luas daun), biomassa tanaman, dan property dari kimia tanah (pH (H2O), karbon  organik  dan   total nitrogen). Aplikasi dari ekstrak bunga matahari Meksiko dua kali seminggu ke media tanah menghasilkan tinggi tanaman, jumlah daun, luas daun dan total biomassa tanaman yang lebih baik dibandingkan perlakuan lainnya. Hasil ini menunjukkan bahwa ekstrak bunga matahari Meksiko dapat menggantikan peran dari pupuk kandang sapi dan sekam bakar sebagai sumber nutrisi bagi bibit pisang.